Interaction between whey protein and soy lecithin and its influence on physicochemical properties and in vitro digestibility of emulsion: A consideration for mimicking milk fat globule. (January 2023) - Ma, Qian; Ma, Shuaiyi; Zhao, Yanjie; Sun, Meng; Li, Xiaodong; Liu, Lu; Zhang, Xiuxiu; Sun, Yue; Fanny Massounga Bora, Awa; Tian, Songfan; Zhang, Qiumei; Leng, Youbin
Graphical abstract: Highlights: WP formed complexes with SL through hydrophobic and electrostatic interaction. Interaction changed the secondary structure of WP and enhanced hydrophobicity. The emulsions prepared by SL to WP (1:3) showed better physical properties. Digestive properties of the prepared emulsion were similar to that of human milk. Addition of SL increased the fat digestion and the release of free fatty acids. Abstract: In this study, from the perspective of simulating the milk fat globule (MFG) emulsion, the interaction between soybean lecithin (SL) and the main protein in milk, whey protein (WP), and its effect on physical characteristics and lipid digestion were investigated through multiple spectroscopic techniques and in vitro digestion. The mechanism of SL and WP was static quenching, indicating that a complex formed between WP and SL through hydrophobic interaction and hydrogen bonding. The addition of SL changed the secondary structure of WP. When the ratio of SL to WP was 1:3, the obtained SL–WP emulsion that simulated milk fat globule exhibited the smallest particle size distribution and the highest absolute value of zeta potential. In addition, the emulsion exhibited high encapsulation efficiency (91.67 ± 1.24 %) and good stability. Compared with commercially available infant formula (IF), the final free fatty acid release of prepared SL–WP emulsion was close to that of human milk (HM). The addition of lecithin increased the digestibility of fat and the release of free fatty acids, and the digestive characteristic and particle size change also were closer to that of HM from results of kinetics of free fatty acid release and microstructure analysis.